Into the night cabarets and clubs in modern art - Ostende, Florence 1983-; Johnson, Lotte ca. 20. Jh (Prestel, 2019)
"Ranging from the 1880s to the 1960s, this richly illustrated history of cafés, cabarets and clubs in modern art includes both famed and little-known sites of the avant-garde. Organised by city, 'Into the Night' presents an exhilarating journey into a selection of social spaces across the world, from New York to Tehran, Paris, Mexico City, London, Berlin, Vienna, Ibadan and beyond. Bringing together painting, drawing, photography, sculpture, performance, film and archival material, this publication highlights the work of artists, performers, designers, musicians and writers such as Henri de Toulouse-Lautrec, Loïe Fuller, Josef Hoffmann, Wyndham Lewis and Giacomo Balla, as well as Ramón Alva de la Canal, Theo van Doesburg, Sophie Taeuber-Arp, Jeanne Mammen, Anita Berber, Aaron Douglas, Jacob Lawrence, Colette Omogbai, Twins Seven-Seven and Parviz Tanavoli. Fourteen newly commissioned essays, accompanied by numerous artworks and rarely seen ephemera, explore how these unique spaces fostered a spririt of experimentation and collaboration, sparking new forms of artistic expression."
Cover title
Catalogue of an exhibition held at the Barbican Art Gallery, London, 4 October 2019 - 19 January 2020; and Belvedere, Vienna, 14 February - 1 June 2020
Keywords: Geschichte 1880-1969; Kabarett; Künstler; Künste; Kaffeehaus -- Motiv; Avantgarde; Kaffeehaus; Nachtleben -- Motiv; Nachtklub; Nightlife in art / Exhibitions; Nightclubs / Pictorial works; Music-halls (Variety-theaters, cabarets, etc.) / History; Music-halls (Variety-theaters, cabarets, etc.) / Pictorial works; Art, Modern / 20th century / History; Art, Modern; Music-halls (Variety-theaters, cabarets, etc.); 1900-1999; History; Pictorial works; Exhibition catalogs; Essays; Illustrated works; Ausstellungskatalog -- Barbican Art Gallery -- 04.10.2019-19.01.2020 -- London; Ausstellungskatalog -- Belvedere -- 14.02.2020-01.06.2020 -- Wien; Bildband